2013
DOI: 10.4103/1947-2714.112481
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular mass formulae and prevalence rates of echocardiographic left ventricular hypertrophy in Nigerians with essential hypertension

Abstract: Background:Left ventricular hypertrophy (LVH) as a marker of cardiac damage in hypertension has important prognostic implications. With high prevalence of hypertension in Nigeria and the untoward effect of LVH, it is essential that the prevalence of LVH be determined.Aims:To determine prevalence of LVH and its severity in clinical practice among hypertensive patients referred for echocardiographic assessment in Nigeria.Materials and Methods:Devereux and Troy formulae were used to calculate echocardiographic LV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(29 reference statements)
1
1
1
Order By: Relevance
“…The frequency of LVH in our study is quite similar to the 95.5% reported by Ulasi et al [26] among 98 Nigerian hypertensive patients with RKF stage 4 and 5. It is however somewhat higher than the 74.2% [27], 62.7% [20], 38.9% [28], 51.3% [29] and 34% [30] that were observed in other studies of Nigerian patients. Niakara et al [31] in Burkina Faso reported a frequency of 53.3% clearly lower than ours.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The frequency of LVH in our study is quite similar to the 95.5% reported by Ulasi et al [26] among 98 Nigerian hypertensive patients with RKF stage 4 and 5. It is however somewhat higher than the 74.2% [27], 62.7% [20], 38.9% [28], 51.3% [29] and 34% [30] that were observed in other studies of Nigerian patients. Niakara et al [31] in Burkina Faso reported a frequency of 53.3% clearly lower than ours.…”
Section: Discussioncontrasting
confidence: 58%
“…Nardi et al [24] found that values of LVM progressively increased from CKD stage 2 to 5. An inverse association between LVM and GFR was also reported by Redon et al [25] In Sub-Saharan Africa [20] [26]- [28], the prevalence of LVH in hypertensive patients with RKF has generally been reported to be elevated. The frequency of LVH in our study is quite similar to the 95.5% reported by Ulasi et al [26] among 98 Nigerian hypertensive patients with RKF stage 4 and 5.…”
Section: Discussionsupporting
confidence: 56%
“…A study in Pakistan, for instance, revealed that women were 11.35 times more likely to develop LVH than the male counterparts even after adjusting for other factors [ 37 ]. Similarly, studies in Nigeria [ 38 ], China [ 12 ] and the LIFE (losartan intervention for endpoint reduction in hypertension) study [ 39 ] showed a trend towards a higher prevalence in women. However, some studies from European countries have shown a higher prevalence in men [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 88%